Lin28 proteins promote expression of 17∼92 family miRNAs during amphibian development. Issue 1 (14th November 2015) - Warrander, Fiona; Faas, Laura; Kovalevskiy, Oleg; Peters, Daniel; Coles, Mark; Antson, Alfred A.; Genever, Paul; Isaacs, Harry V.
Abstract : Background: Lin28 proteins are post‐transcriptional regulators of gene expression with multiple roles in development and the regulation of pluripotency in stem cells. Much attention has focussed on Lin28 proteins as negative regulators of let‐7 miRNA biogenesis; a function that is conserved in several animal groups and in multiple processes. However, there is increasing evidence that Lin28 proteins have additional roles, distinct from regulation of let‐7 abundance. We have previously demonstrated that lin28 proteins have functions associated with the regulation of early cell lineage specification in Xenopus embryos, independent of a lin28/ let‐7 regulatory axis. However, the nature of lin28 targets in Xenopus development remains obscure.Results: Here, we show that mir‐17∼92 and mir‐106∼363 cluster miRNAs are down‐regulated in response to lin28 knockdown, and RNAs from these clusters are co‐expressed with lin28 genes during germ layer specification. Mature miRNAs derived from pre‐mir‐363 are most sensitive to lin28 inhibition. We demonstrate that lin28a binds to the terminal loop of pre‐mir‐363 with an affinity similar to that of let‐7, and that this high affinity interaction requires to conserved a GGAG motif.Conclusions: Our data suggest a novel function for amphibian lin28 proteins as positive regulators of mir‐17∼92 family miRNAs. Developmental Dynamics 245:34–46, 2016 . © 2015 Wiley Periodicals, Inc. Key Findings: We show that mir‐17∼92 and mir‐106∼363 cluster miRNAs are down regulated in response to lin28 knockdown in Xenopus embryos. We demonstrate that lin28a binds to the terminal loop of pre‐mir‐363 and this interaction requires a conserved a GGAG motif. Our data suggest a novel function for amphibian lin28 proteins as positive regulators of mir‐17∼92 family miRNAs.